State-space averaged modeling and transfer function derivation of DC-DC boost converter for high-brightness led lighting applications - Muhammad Wasif Umar; Norzaihar Yahaya; Zuhairi Baharudin (Universitas Ahmad Dahlan, 2019)
This paper presents dynamic analysis of a boost type DC-DC converter for high-brightness LED (HBLED) driving applications. The steady state operation in presence of all system parasitics has been discussed for continuous conduction mode (CCM). The state-space averaging, energy conservation principle and standard linearization are used to derive ac small signal control to inductor current open-loop transfer function of the converter. The derived transfer function can be further used in designing a robust feed-back control network for the system. In the end frequency and transient responses of the derived transfer function are obtained for a given set of component values, hence to provide a useful guide for control design engineers.